Tatalaksana Pemeriksaan Thorax Pada Bayi Dengan Kasus Berat Badan Lahir Rendah (BBLR) Di Instalasi Radiologi RS Islam Faisal Makassar - Wahyuddin Wahyuddin; AR.Rakhmansyah Iskandar; Nur Halisa Tul Ma’rifa (Lontara Journal of Health Science and Technology, 2020)
LBW is one indicator to see how the degree or health status of children, so it plays an important role to monitor how the health status of children from birth. This study aims to find out how to administer Thorax Examination in Infants with a West Low Birth (BBLR) case at Faisal Makassar Islamic Hospital. In the research method, the writer uses qualitative research with a descriptive approach. From the results of the research conducted it can be concluded that the management of Thorax examination in infants with cases of Low Birth Weight (LBW) in Faisal Islamic Hospital Makassar Antero Posterior projection (AP) is said to be enough to optimally diagnose the doctor's reading results namely bilateral pneumonia.